Pengaruh Fasilitas, Keberagaman Produk, Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian di Supermarket Syariah (Studi Kasus PT. Cepat Versi Arli Singkawang) - Hendrawan, Hendrawan; Wahyudi, Wahyudi; Ardelia, Aya Sofia; Achmad, Achmad (Jurnal Ilmiah Ekonomi Islam, 2024)
The study aims to determine the effect of facilities, product diversity, price, and service quality on purchasing decisions at Islamic supermarkets (PT. Cepat Versi Arli) Singkawang City. This study consists of independent variables of facilities, product diversity, price and service quality, dependent variables of service decisions. The type of research used is descriptive quantitative research. The population in this study were customers who had shopped at PT. Cepat Versi Arli Singkawang City. The data collection technique uses the distribution of questionnaires with questions or statements that have been provided and distribution via g-form. The sample taken amounted to 100 respondents. The analysis method used is multiple linear regression analysis with the SPSS version 26. The results showed that partially the facility variable had a positive and significant effect on purchasing decisions, product diversity had a positive and insignificant effect on purchasing decisions, price had a positive and significant effect on purchasing decisions, service quality had a positive and significant effect on purchasing decisions. Simultaneously, the variables of facilities, product diversity, price and service quality have a positive and significant effect on purchasing decisions.